Keadilan Gender dalam Hukum Waris Islam: Studi Komparatif antara Hukum Waris Faraid dan Prinsip Kesetaraan Gender di Era Modern - Rozi, A. Fahrur (Prodi HKI IAI Miftahul Ulum Pamekasan, 2024)
This study explores gender justice within the framework of Islamic inheritance law, focusing on a comparative analysis between the faraid system and modern principles of gender equality. The faraid system, as a classical Islamic legal framework, strictly regulates inheritance distribution, including gender-based differences in shares. In contrast, the principle of gender equality demands equal treatment of men and women in all aspects of life, including inheritance rights. This research aims to examine how faraid can be contextually interpreted to achieve substantive justice for women while upholding the core principles of Islamic law. Using a qualitative approach and comparative analysis, the study finds that there is room for ijtihad in the application of Islamic inheritance law, allowing for a balance between normative Islamic justice and contemporary demands for gender equality.